Stres Kerja dan Beban Kerja sebagai Pendorong Kinerja Karyawan: Bukti Empiris dari Instansi Pelayanan Publik - Rakarian Widhamurti Maylova; Sri Rahayu; Rifda Fitrianty (BISMA : Business and Management Journal, 2026)
This study employed an explanatory-correlational quantitative survey method applied to the entire population of 130 permanent employees with a minimum of one year of service. Data were collected using a 5-point Likert scale instrument (22 items) that had been tested for validity and reliability. Multiple linear regression analysis using SPSS version 26 statistical software showed that job stress (β = 0.451; p < 0.001) and workload (β = 0.553; p < 0.001) had a significant positive effect on employee performance, with workload having a relatively more dominant contribution. The regression model explains 52.3% of the variation in performance (Adjusted R² = 0.523). These findings confirm the concept of eustress and reinforce the JD-R theory that job demands can enhance performance when balanced by adequate job resources. Practically, management at the KPKNL and similar public sector agencies is advised to shift the stress management paradigm from a stress reduction approach toward stress optimization through proportional task distribution, the utilization of digital technology, and the development of employee competencies to maintain stress and workload at constructive levels.